Design and Implementation of a Tuition Payment Administration Information System Using the Laravel Framework at SMA Wachid Hasyim 1 Central Surabaya - Ainul Fiky; Didik Tristanto (Journal of Science Technology (JoSTec), 2025)
SMA Wachid Hasyim 1 is an educational institution under the Wachid Hasyim Foundation, established on January 31, 1967. Currently, tuition and book (LKS) payments at SMA Wachid Hasyim 1 are still processed manually by recording them in a payment logbook. In this research, the waterfall method is used, where the application is first designed and then implemented. To address this issue, the author designed and built a web-based Tuition Payment Information System using the Laravel framework. This system aims to simplify the payment process by allowing transactions through the website, uploading proof of payment, and generating payment reports. The result of this application is to ease student payments and transaction record-keeping. Keywords: SPP Payment, Information System, Website